Legal Provision Affecting Real Estate Tax Delinquencies, Tax Sales, and Redemptions (Book). - Bennett, O. (The Accounting Review, 1934)
Reviews the book "Legal Provision Affecting Real Estate Tax Delinquencies, Tax Sales, and Redemptions," by M.H. Hunter.